Student field trip to mangrove forests: The effect on learning outcomes - Rangga, Beni Egidius; Lidi, Maria Waldetrudis; Daud, Maimunah H.; Wolo, Daniel (Inornatus: Biology Education Journal, 2023)
The low student learning outcomes are also because many students are less active in asking questions, student activities are still passive and only centered on the teacher. Mangrove forest is a place that can be used as a source of student learning. Field trips to mangrove forests are a form of learning that can help strengthen students' knowledge. The research aims to test field trips to mangrove forests on student learning outcomes. Experimental study without a control class on 20 students of SMA Mangipanda in Ende. Learning achievement tests are used to collect data. Data analysis using the Wilcoxon test. The findings show that the sig. < 0.05. This finding indicates that the field trip method to the mangrove forest has an effect on the learning outcomes of class X students of SMA Negeri Magepanda.